Mosaic Drug Efflux Gene Sequences from Commensal Neisseria Can Lead to Low-Level Azithromycin Resistance Expressed by Neisseria gonorrhoeae Clinical Isolates - William M. Shafer (American Society for Microbiology, 2018)
ABSTRACT In a previous mBio article, Wadsworth and colleagues (mBio 9:e01419-18, 2018, https://doi.org/10.1128/mBio.01419-18) described Neisseria gonorrhoeae isolates that express low levels of azithromycin (Azi) resistance. Whole-genome sequencing and bioinformatic analysis suggested that the isolates had acquired DNA from commensal Neisseria spp. that caused numerous nucleotide changes in the mtr locus, which contains genes for a transcriptional repressor (MtrR) and three proteins (MtrC-MtrD-MtrE) that form a multidrug efflux pump known to export macrolides. Strong regions of linkage disequilibrium mapped to the overlapping mtrR and mtrCDE promoters and mtrD. Genetic analyses revealed that these mosaic-like sequences increased transcription of mtrCDE and MtrD function, respectively. These changes also had strong epistatic effects that collectively were responsible for decreased susceptibility to MtrCDE substrates, including Azi. The report emphasizes the importance of gene exchange among neisserial species and development of antibiotic resistance in gonococci, both of which have ramifications for detection of resistance markers and efficacy of antibiotic treatment regimens for gonorrhea.